DAMPAK PERUBAHAN IKLIM TERHADAP USAHA APEL DI KECAMATAN PONCOKUSUMO KABUPATEN MALANG - Juli Rahaju; Muhandoyo Muhandoyo (Fakultas Pertanian Universitas Yudharta Pasuruan, 2017)
Climate change has a significant imp act in the fields of agricultur e ,  b ecause  agriculture has a heavy reliance on climate elements . Therefore , studies on the  impa ct of climate change on agriculture is important to study . This case study was  conducted in Poncokusumo , Malang Regency for 7 months . Subjects were apple  growers who have made  apple cultivation for 10 years or more and still trying to  apple today . Th e research object is climate change with the elements that will be  Studied include temperature, humidity and rainfall and Adaptation Efforts that have  been done the farmer . The results Showed that both climatic elements of  temperature, humidity and rainf all simultaneously Contribute Significantly to the  productivity of the apple . Separately rainfall only significant role . Respondents  who did the adaptation as much as 85.29 % of the total respondents . Form of  adaptation by farmers are watering the plant s to cope with high temperatures ,  intercropping to address the decline in income from apples , the reduction of more  branches to cope with the humidity and spraying pesticides more intensively to  address the incidence of diseases by the caused by rainfall and high humidity .